لبعض المضائف الوسطية في محافظة ذي قار Echinococcusis دراسة وبائية لداء المشوكات الحبيبية - عيسى البدران عدنان; عباس العبادي فاضل; سعدون الغزي زهراء (University of Thi-Qar Journal of Science, 2010)
The present study designated to throw more light on the prevalence of Echinococcosis slughter livestock animals at Thi-Qar abattior.The samples of the animals were 566 cases .It was found that 76 animals which were infected with hydatid disease including (31 cattles, 20 sheeps, 10 camels, 8 goats and 7 buffaloes). The cattle were higlly infected (20.67% ) while the lowest infection was in buffaloes ( 7.96% ) .It also concluded that the among females was 56.58% which was higher than the males 43.42% .It was also noted that percentage infection with hydatid disease was increased with the increase of the animals age.The percentage was highest among animals in age 4 years or older 19.49% and the lowest was 8.18% among those less than 2 years old.The present study show that liver was the higly infected organ (14.02%) follwed by lungs (12.23%).It included infection percentage according to seasonal variation. The highest infection percentage was 23.50% in Winter and lowest 1.10% in Summer